Peningkatan Efektivitas dan Akuntabilitas Program Koin NU sebagai Instrumen Pemberdayaan Masyarakat - Saputra, Moh. Maher Eka; Raishania, Raishania Muhiba Salafi; Syafita, Venti Dina; Saputra, Weka Rendra; Adhitya, Toni (Welfare : Jurnal Pengabdian Masyarakat, 2026)
The Koinisasi (NU Coin) program is a philanthropic movement initiated by PBNU (Nahdlatul Ulama Executive Board) to collect community funds through community participation. These funds are used to support social, religious, and community empowerment activities. In NU Care Lazisnu MWCNU Prambon-Nganjuk, this program plays an important role in strengthening organizational independence and improving community welfare. Therefore, for the program to be sustainable, optimization is needed to ensure good governance and effectiveness of Koinisasi. This community service aims to optimize the governance and effectiveness of the NU Koin program in MWCNU Lazisnu Prambon Nganjuk. The method used in the research is participatory action research. The results of the community service show that the program runs routinely and is organized, the program has also been proven to support social activities and help communities in need, however, there are still obstacles in the collection mechanism in each mengomel which is considered less effective and efficient. This program has implemented the principles of transparency and accountability. However, the effectiveness of collection and strengthening of the governance system are still needed for the program to be more optimal, sustainable, and able to increase public trust.